Three dimensional microbubble dynamics near a wall subject to high intensity ultrasound - Wang, Q. X.; Manmi, K. (Physics of fluids (1994), 2014)
Dynamics of cavitation microbubbles due to high intensity ultrasound are associated with important applications in biomedical ultrasound, ultrasonic cleaning, and sonochemistry. Previous numerical studies on this phenomenon were for an axisymmetric configuration. In this paper, a computational model is developed to simulate the three dimensional dynamics of acoustic bubbles by using the boundary integral method. A bubble collapses much more violently subjected to high intensity ultrasound than when under normal constant ambient pressure. A few techniques are thus implemented to address the associated numerical challenge. In particular, a high quality mesh of the bubble surface is maintained by implementing a new hybrid approach of the Lagrangian method and elastic mesh technique. It avoids the numerical instabilities which occur at a sharp jet surface as well as generates a fine mesh needed at the jet surface. The model is validated against the Rayleigh-Plesset equation and an axisymmetric model. We then explore microbubble dynamics near a wall subjected to high intensity ultrasound propagating parallel to the wall, where the Bjerknes forces due to the ultrasound and the wall are perpendicular to each other. The bubble system absorbs the energy from the ultrasound and transforms the uniform momentum of the ultrasound parallel to the wall to the highly concentrated momentum of a high-speed liquid jet pointing to the wall. The liquid jet forms towards the end of the collapse phase with a significantly higher speed than without the presence of ultrasound. The jet direction depends mainly on the dimensionless standoff distance γ = s/Rmax of the bubble from the wall, where s is the distance between the wall and the bubble centre at inception and Rmax is the maximum bubble radius. The jet is approximately directed to the wall when γ is 1.5 or smaller and rotates to the direction of the ultrasound as γ increases. When γ is about 10 or larger, the wall effect is negligible and the jet is along the acoustic wave direction. When the amplitude of the ultrasound increases, the jet direction does not change significantly but its width and velocity increase obviously.